Legal aspects of the use of social media accounts: сurrent state and perspectives - Некіт, Катерина Георгіївна; Некит, Екатерина Георгиевна; Nekit, Ekaterina G.; Некіт, К. Г.; Nekit, Kateryna H. (Institute of State and Law of the Academy of Sciences of the Czech Republic, 2020)
This article analyzes the concept and legal nature of social media accounts to explore whether these can become the object of civil-law rights, particularly, an object of property or so-called virtual property rights. It examines the essence of a social media account and reveals the possibility of distinguishing specific elements in its structure. Some problems connected to social media accounts including liability for its content to the opportunity to purchase an account are investigated. The recent case law concerning business accounts is analyzed. The conclusion is made that every company should develop its own policy concerning social networks where all possible consequences connected with the rights in relation to social media accounts of the company would be specified, as there is no uniform court practice on this issue. The article also considers, whether it is possible to inherit a social media account. This takes into account approaches in various countries to the problem of determination of the post-mortem fate of digital assets, which shows a unified tendency to consider social media accounts as part of the estate transferred to the heir

У цій статті аналізується концепція та юридична природа облікових записів (акаунтів) в соціальних мережах, щоб з’ясувати, чи можуть вони стати об’єктом цивільно-правових прав, зокрема об’єктом власності чи так званими правами віртуальної власності. Досліджується зміст облікового запису в соціальних мережах та виявляється можливість виділення конкретних елементів у його структурі. Досліджуються деякі проблеми, пов’язані з обліковими записами в соціальних мережах, включаючи відповідальність за його вміст та можливість придбання облікового запису. Проаналізовано нещодавню судову практику щодо господарських рахунків. Зроблено висновок, що кожна компанія повинна розробити власну політику щодо соціальних мереж, де були б зазначені всі можливі наслідки, пов’язані з правами щодо облікових записів компанії в соціальних мережах, оскільки єдиної судової практики з цього питання немає. У статті також розглядається, чи можна успадкувати обліковий запис у соціальних мережах. Для цього потрібне врахування підходів різних країн до проблеми визначення посмертної долі цифрових активів, що демонструє єдину тенденцію розглядати акаунти в соціальних мережах як частину спадщини, переданої спадкоємцю.

В этой статье анализируется концепция и юридическая природа учетных записей (аккаунтов) в социальных сетях, чтобы выяснить, могут ли они стать объектом гражданско-правовых прав, в частности объектом собственности или так называемыми правами виртуальной собственности. Исследуется содержание аккаунта в социальных сетях и определяется возможность выделения конкретных элементов в его структуре. Исследуются некоторые проблемы, связанные с учетными записями в социальных сетях, включая ответственность за их содержание и возможность приобретения учетной записи. Проанализирована недавняя судебная практика относительно хозяйственных счетов. Сделан вывод, что каждая компания должна разработать собственную политику в отношении социальных сетей, где были бы указаны все возможные последствия, связанные с правами на учетных записей компании в социальных сетях, поскольку единой судебной практики по этому вопросу нет. В статье также рассматривается, можно ли унаследовать аккаунт в социальных сетях. Для этого нужно учитывать подходы различных стран к проблеме определения посмертной судьбы цифровых активов, что демонстрирует единую тенденцию рассматривать аккаунты в социальных сетях как часть наследства, переданного наследнику.
Nekit K. Legal aspects of the use of social media accounts: сurrent state and perspectives / K. Nekit // The Lawyer Quarterly. – V. 10 (3). – Institute of State and Law of the Academy of Sciences of the Czech Republic, 2020. – P. 305-323.
Keywords: social media; account; digital assets; inheritance; virtual property; personal data; соціальні мережі; акаунт; цифрові активи; спадщина; віртуальна власність; персональні дані; социальные сети; аккаунт; цифровые активы; наследство; виртуальная собственность; персональные данные; Research Subject Categories::LAW/JURISPRUDENCE